Women Friendly Mosque in Banda Aceh: A Study of the Concept of Gender Justice and Gender Planning Perspective - Fadlia, Faradilla; Ramadani, Ismar; Zalikha, Siti Nur (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2021)
This paper analyzed how several mosques as a public space are not friendly to one gender group. Mosques as public spaces should be accessible to everyone and must accommodate the needs of all gender groups. This study seeks to see how the spatial arrangement that is not friendly to women impacts the comfort of women to worship in the mosque. In addition, this study also tries to analyze mosques in Banda Aceh, which are considered gender-responsive. This study uses qualitative methods with in-depth interviews and uses gender planning theory as an analytical tool. This study found several findings. First, the comfort and discomfort related to the arrangement of space and facilities are experienced by female congregations and male congregations. Second, assumptions that affect spatial planning and facilities have discriminated against one gender group. Third, mosques in Aceh are generally intended for men; this results in the layout of the mosque not accommodating the needs of women.